Changes in Bleaching Susceptibility among Corals Subject to Ocean Warming and Recurrent Bleaching in Moorea, French Polynesia - Pratchett, Morgan S.; McCowan, Dominique; Maynard, Jeffrey A.; Heron, Scott F. (PloS one, 2013)
Climate-induced coral bleaching poses a major threat to coral reef ecosystems, mostly because of the sensitivities of key habitat-forming corals to increasing temperature. However, susceptibility to bleaching varies greatly among coral genera and there are likely to be major changes in the relative abundance of different corals, even if the wholesale loss of corals does not occur for several decades. Here we document variation in bleaching susceptibility among key genera of reef-building corals in Moorea, French Polynesia, and compare bleaching incidence during mass-bleaching events documented in 1991, 1994, 2002 and 2007. This study compared the proportion of colonies that bleached for four major genera of reef-building corals (Acropora, Montipora, Pocillopora and Porites), during each of four well-documented bleaching events from 1991 to 2007. Acropora and Montipora consistently bleached in far greater proportions (up to 98%) than Pocillopora and Porites. However, there was an apparent and sustained decline in the proportion of colonies that bleached during successive bleaching events, especially for Acropora and Montipora. In 2007, only 77% of Acropora colonies bleached compared with 98% in 1991. Temporal variation in the proportion of coral colonies bleached may be attributable to differences in environmental conditions among years. Alternately, the sustained declines in bleaching incidence among highly susceptible corals may be indicative of acclimation or adaptation. Coral genera that are highly susceptible to coral bleaching, and especially Acropora and Montipora, exhibit temporal declines in their susceptibility to thermal anomalies at Moorea, French Polynesia. One possible explanation for these findings is that gradual removal of highly susceptible genotypes (through selective mortality of individuals, populations, and/or species) is producing a coral assemblage that is more resistant to sustained and ongoing ocean warming.